A protocol for a nationwide multicentre, prospective surveillance cohort and nested- consented cohort to determine the incidence and clinical outcomes of slipped capital femoral epiphysis. (March 2020) - Perry, D. C.; Arch, B.; Appelbe, D.; Francis, P.; Spowart, C.; Knight, M.
No abstract available